GAMBARAN PENGETAHUAN IBU DALAM PERAWATAN PERIANAL DENGAN KEJADIAN DIAPER DERMATITIS PADA BAYI USIA 9-12 BULAN DI POSYANDU PUSKESMAS CIMAREME TAHUN 2020 - Budi Somantri (Jurnal Kesehatan Rajawali, 2020)
Background: Diaper dermatitis can be a rash in the diaper area. Based on data released by the World Health Organization (WHO) in 2012, the prevalence of skin irritation (diaper dermatitis) in infants is quite high, 25% of 6,840,507,000 babies born in the world, mostly suffer from skin irritation (diaper dermatitis) due to diaper use. The highest number was found at the age of 9-12 months. Objectuve: To describe the knowledge of mothers in perianal care with the incidence of diaper dermatitis in infants aged 9-12 months at Posyandu Puskesmas Cimareme in 2020. Methods: This study used a quantitative descriptive method. The sample in this study amounted to 107 respondents. The sampling technique was purposive sampling. The test used is the frequency distribution. Results: 42 respondents (39.3%) had good knowledge, 69 respondents (64.5%) did not experience diaper dermatitis. Conclusion: It can be concluded from this study that mothers who have less knowledge, the majority of their babies experience diaper rash. This is influenced by the mother's ignorance about how to care for the baby properly. It is hoped that health workers will be able to provide information on how to care for babies properly so that diaper rash does not occur in babies